Dynamics of gender-based violence in Scopus Indexed Publication 2014-2024: A bibliometric analysis - Zuhdi, Dzakwan Amar; Sulistyanto, Ari; Harahap, Hamida Syari (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
One negative effect of the proliferation of social media and other forms of online communication on women is the rise of gender-based violence in this space. This study seeks to trace the evolution of this field of study from 2014 to 2024 by looking at topics/issues, author/country collaboration, publication trends, and relevant sources. This research uses the Bibliometric analysis method sourced from the Scopus database. 101 articles were obtained through a filter process using the PRISMA model. The data was processed using Vosviewer and R Studio Biblioshiny software to analyze and visualize the data. The results showed that the development of publications each year occurred most in 2022, with 26 publications. The main topics in this study were obtained from the co-occurrence keyword analysis of as many as 9 clusters, with the 2 most clusters, namely Digital Gender Violence and Misogyny. The United States is the most productive country to publish. Overall, this research can be a valuable reference for researchers in determining the direction of future research.